New species of Szelenyiopria Fabritius and description of the male of Szelenyiopria distinguenda (Loiácono) (Hymenoptera: Diapriidae) - Comério, Emerson Fraga; Oliveira, Ana Lígia Santos; Periotto, Nelson Wanderley; Lara, Rogéria Inês Rosa (EntomoBrasilis, 2019)
Abstract. Here are described and ilustrated Szelenyiopria loiaconae sp. nov., Szelenyiopria jataiensis sp. nov., and the male of Szelenyiopria distinguenda (Loiácono) (Hymenoptera, Diapriidae). Novas espécies de Szelenyiopria Fabritius e descrição do macho de Szelenyiopria ditinguenda (Loiácono) (Hymenoptera: Diapridae) Resumo. Neste estudo, são descritas e ilustradas Szelenyiopria loiaconae sp. nov., Szelenyiopria jataiensis sp. nov., e o macho de Szelenyiopria distinguenda (Loiácono) (Hymenoptera, Diapriidae).